Penyuluhan Peran Remaja dalam Mencegah Stunting Melalui Siaran RRI Pro 1 Cirebon Kerja Sama dengan Pimpinan Daerah Aisyiyah Kabupaten Cirebon - Marwati Marwati; Sofiyati Sofiyati (Jurnal Kabar Masyarakat, 2025)
Stunting is a chronic nutritional problem that has a broad impact on children's physical and cognitive development, and contributes to the intergenerational cycle of malnutrition. Teenagers have a strategic role in preventing stunting because they are future parents. This community service activity aims to increase teenagers' knowledge about stunting, the importance of balanced nutrition, as well as risk factors and prevention of stunting. Counseling was carried out via broadcast on RRI Pro 1 Cirebon in collaboration with the Aisyiyah Regional Leadership of Cirebon Regency. The methods used include lectures and question and answer sessions guided by radio broadcasters. The results of the activity show an increase in teenagers' understanding of healthy lifestyles and the importance of balanced nutrition in preventing stunting. Through their role as agents of change, teenagers are expected to be able to disseminate information and contribute to creating a healthier and more productive generation. Involving teenagers in efforts to prevent stunting is a strategic step in improving the quality of public health in a sustainable manner.